The Psychological Skill Level of Bengkulu Athletes During the Covid-19 Pandemic - Yahya Eko Nopiyanto; Septian Raibowo; Novriansyah Novriansyah; Fitri Agung Nanda (JUARA : Jurnal Olahraga, 2021)
The Covid-19 pandemic has had a tremendous impact on sporting events. This research aimed to determine the psychological skill level of Bengkulu PON athletes during the Covid-19 pandemic. The research method used in this study was a quantitative descriptive method with a survey approach. The subjects of this research were all athletes of PON Bengkulu, with a total of 83 athletes. The data of the research variable was collected using a questionnaire, "The Psychological Skills Inventory for Sports (PSIS)," adopted from (Mahoney, Gabriel & Perkins, 1987). The validity of this instrument was 0.797-0.801, while the reliability was 0.795. The researcher used the mean ideal and standard deviation to analyze the research data. The result of this research showed that: (1) aspect of motivation was a high category with 57.8%; (2) aspect of self-confidence was a high category with 66%; (3) aspect of anxiety control was a high category with 67.3%; (4) aspect of mental preparation was a high category with 56.6%; (5) aspect of team emphasize it was high category with 51.8%; (6) aspect of concentration with 48%. This research concluded that the psychological skill level of PON Bengkulu athletes during the Covid-19 pandemic was in the high category.